PELAKSANAAN PENYIDIKAN TERHADAP PELAKU TINDAK PIDANA PERBANKAN OLEH DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU - Nofrianto, Koko; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Financial institutions have a role as a financial intermediary (financial intermeditary) which as an institution conducting fund raising from the public in the form of savings and channel them to the public in the form of credit or financing. The continued development of financial institutions increasingly widespread criminal offenses against the financial institutions. Including in Riau, a growing number of criminal acts is also banking on Riau. Investigation process of banking criminal acts in Riau region still faces many obstacles, it is seen from the cases that terminated or are still in the process of investigation. This is certainly an obstacle in the process of investigation of cases that occurred around the time that will come. Crime in banking criminal acts are often exposed for their reports information provided by the parties. Therefore it is necessary the interrogation of criminal offenses banking efisisen by Riau Police. The purpose of this thesis, namely: First, How is the implementation of banking Investigation on criminal offenses by the Special Criminal Investigation Police of Riau; Secondly, What are the obstacles in the implementation of banking Investigation of criminal acts by the Special Criminal Investigation Police of Riau; Third, How the efforts made to overcome the obstacles to the implementation of banking Investigation of criminal offenses by the Special Criminal Investigation Police of Riau.Keywords: Crime Peyidikan- Banking